Pengaruh pemberian DIIT nasi jagung dan nasi putih dengan perbandingan 1:1 terhadap perubahan kadar glukosa darah pasien diabetes melitus - Meiranda, Bella Dwi; Kurniasari, Septi; Andora, Novika (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2025)
Background: Diabetes Mellitus (DM) is a chronic metabolic disease characterized by high blood sugar levels. This condition can lead to the pancreatic gland's inability to produce insulin optimally, preventing the body from perfectly processing consumed sugar. Purpose: To determine the effect of consuming corn rice mixed with white rice on blood glucose levels in patients with diabetes mellitus Method: Quantitative research with Pre Experimental research design (one group Pre Post Test Design). The method used is saturated sampling. The subjects of this study were people with diabetes mellitus who were given corn rice, namely 1: 1 in processed white rice and corn rice weighing 150 grams accompanied by side dishes. Results: Bivariate analysis obtained a p value of 0.000 (a <0.05) so that it was stated that there was an effect of giving DIIT corn rice with a ratio of 1:1 corn rice and white rice in patients with diabetes mellitus. Conclusion: There is an effect of giving a corn rice diet with a 1:1 ratio of corn rice and white rice on diabetes mellitus sufferers.   Keywords: Diabetes Mellitus; Corn Rice.   Pendahuluan: Diabetes Melitus atau DM adalah penyakit atau gangguan metabolisme kronis yang ditandai dengan tingginya kadar gula darah. Hal ini bisa menyebabkan kelenjar pankreas tidak dapat memproduksi hormon insulin secara optimal, sehingga tubuh tidak dapat memproses gula yang dikonsumsi secara sempurna. Tujuan: Untuk mengetahui pengaruh pemberian nasi jagung yang dicampur nasi putih terhadap kadar gula darah glukosa pada penderita diabetes mellitus Metode: Penelitian kuantitatif dengan desain penelitian Pre Eksperimental (one group Pre Post Test Design). Metode yang digunakan yaitu sampling jenuh. Subjek penelitian ini adalah masyarakat penderita diabetes melitus dengan pemberian nasi jagung yaitu 1:1 pada olahan nasi putih dan nasi jagung dengan berat 150 gram disertai lauk pauk. Hasil: Analisis bivariat diperoleh nilai p=0.000 (a<0.05) sehingga dinyatakan ada pengaruh pemberian DIIT nasi jagung dengan perbandingan 1:1 nasi jagung dan nasi putih pada penderita diabetes mellitus. Simpulan: Ada pengaruh pemberian  nasi jagung dengan perbandingan 1:1 nasi jagung dan nasi putih pada penderita diabetes mellitus.   Kata Kunci : Diabetes Melitus; Nasi Jagung